Inexplicável, inquietante, inconsciente : a subjetividade no romance Esaú e Jacó, de Machado de Assis - Tokashiki, Adriana do Couto (2014)
Published in 1904, Esau and Jacob, Machado de Assis, is a romance that focuses the customs of the bourgeois society of the Rio de Janeiro city of the end XIX century, having as scenario the political context of transition from monarchy to republic, where unrolls scenes of carioca life, private life and political life. A troubled historical period recreated by machadian’s narrative, which causes the speculative and intriguing questions about the puzzles contained in the novel. In the present work, Sigmund Freud is the author, thinker of clinic and culture, invited to dialogue with machadian’s work. The two authors belong to different countries and different social realities, but approaching the fruitful relationship between the world of literature and studies of subjectivity. Despite the differences, the works of the two authors express, each in its own way, certain topics of interest to intellectuals of the late XIX to the XX century: the unknown, the enigmatic, the double, the ambiguous, the stranger, etc. Machado de Assis is a writer who, through a fictional plot, reflects in his works the history, physical space, the everyday and the subjectivity of society. The Esau and Jacob romance, is characterized, by the fact that this effect is recreated with each new reading. In this perspective, the general objective of this research consisted as: to analyze the subjectivity in the narrative of Esau and Jacob. Therefore, we define as the main route to study the presence of “unsettling” (the “uncanny”) in this novel, establishing a comparative study between Machado’s prose and psychoanalytic discourse.